Formação do bailarino intérprete do CEFAR(T) na cidade de Belo Horizonte: desafios, conflitos e contradições - Carla Geruse Gontijo Campolim Moraes (2019)
The present study had as main objective to problematize, from a contemporary perspective, the dance training and its respective methodological approaches, seeking to identify and understand procedures that favored the construction of autonomy and authorality in dance, having as research field the Center of Artistic and Technological Training - CEFART, of the Clóvis Salgado Foundation. To do so, as amethodological resource, a qualitative research process was used, using semistructured interviews, with eighteen people in total, between teachers and students, who acted and performed, from 1987 to 2018. The research revealed the importance of safeguarding and updating CEFART's historical institutional dance collection. It was verified the absence of important documents in the institution, such as programsof shows, lesson plans, political-pedagogical projects, and it was necessary to concentrate the collection of data almost exclusively in the oral source. Despite the absence of official documents, the oral reports made it possible to verify the importance of the institution for the artistic formation and promotion of art in Minas Gerais, highlighting the avant-garde aspect of the original proposal, defining criteria for choosing the coordination and selecting faculty dance, especially in its first threedecades of existence. The theoretical framework that was used as a research source, found agreement and dialogue with concepts that permeate the thoughts of authors such as: the philosopher Michel Foulcaut, who reflects on the docile body; the social educator, Paulo Freire, who points out the need for a pedagogy of autonomy; the researcher Silvie Fortin who reflects on curricula and somatic practices in the training of the dancer; choreographer and theater director KlaussVianna, who understands that dance and life are not separated; the critic and dance specialist Laurence Louppe, which presents the construction of values for a poetics in dance, and researchers Jacques Le Goff and José Carlos Sebe Bom Meihy who focus on writing of History and oral history, respectively, and its relevance to the construction of new knowledge and knowledge.